Pharmacokinetics And Pharmacodynamics Modeling Of Clozapine In Healthy Volunteers And Patients With Schizophrenia Spectrum Disorders Using Pharmacometrics Approach - Orwa, Albitar (2022)
Clozapine is the first-line medication for treatment-resistant schizophrenia. However, it has complex metabolism, an unclear exposure-response relationship, and potential adverse drug reactions (ADRs). The present study aimed to develop an analytical method and pharmacometrics-based models for clozapine and norclozapine pharmacokinetics and pharmacodynamics in healthy volunteers and schizophrenia spectrum disorder (SSD) patients. A surfactant-assisted dispersive liquid-liquid microextraction coupled with HPLC-UV was used for clozapine and norclozapine determination after optimizing experimental factors. 270 data points obtained from 33 healthy volunteers after receiving a single dose of 12.5 mg clozapine were utilized in the semi-physiological pharmacokinetic model development incorporating the pre-systemic clozapine metabolism. To assess clozapine interaction with pantoprazole, a randomized, crossover, open-label study design was implemented. 12 volunteers were given clozapine alone; then clozapine after five days of 40 mg pantoprazole or vice versa, separated by a washout period. Meanwhile, clinical data were extracted from 116 SSD patients’ medical records in Penang General Hospital, with a mean retrospective follow-up of 306 weeks.